2010
DOI: 10.1002/eji.200939485
|View full text |Cite
|
Sign up to set email alerts
|

Parenchymal cells critically curtail cytotoxic T‐cell responses by inducing Bim‐mediated apoptosis

Abstract: To develop cytolytic effector functions, CD8 1 T lymphocytes need to recognize specific Ag/ MHC class I complexes in the context of costimuli on Ag-presenting DC. Thereafter they differentiate into effector and memory CTL able to confer protection against pathogen infection. Using transgenic mice with DC-selective MHC class I expression and DC-specific versus ubiquitous vaccination regimen, we found that DC are sufficient to prime CTL responses. However, Ag recognition on parenchymal non-professional APC negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Mice AND (Tg(TcrAND)53Hed) (37), OT-1 (Tg(TcraTcrb)1100Mjb) (38), invariant chain-moth cytochrome c (Ii-MCC) (Tg(H2-Ea-Cd74/MCC)37GNnak) (39), Ii-reverse transactivator (rTA) (Tg(Cd74-rtTA)#Doi), tet-inducible modified Ii MCC (Tg(tetO-Cd74/MCC)#Doi) (28), CD11c-b 2 m and K14-b 2 m transgenics, and B2m tm1Jae (40), and Cd274 tmiLpc mice (41) have been described previously. Animals were kept on the C57BL/6 (B6) and the B10.BR/SgSnJ (The Jackson Laboratory) backgrounds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice AND (Tg(TcrAND)53Hed) (37), OT-1 (Tg(TcraTcrb)1100Mjb) (38), invariant chain-moth cytochrome c (Ii-MCC) (Tg(H2-Ea-Cd74/MCC)37GNnak) (39), Ii-reverse transactivator (rTA) (Tg(Cd74-rtTA)#Doi), tet-inducible modified Ii MCC (Tg(tetO-Cd74/MCC)#Doi) (28), CD11c-b 2 m and K14-b 2 m transgenics, and B2m tm1Jae (40), and Cd274 tmiLpc mice (41) have been described previously. Animals were kept on the C57BL/6 (B6) and the B10.BR/SgSnJ (The Jackson Laboratory) backgrounds.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we used recipients that were deleted of their b 2 m genes and hence lack MHC class I surface expression but were replete with a transgene expressed in thymic cortical epithelium to allow for the selection of a full T cell compartment, thus reining in lymphopenia-driven proliferation of adoptively transferred CD8 + T cells. Recipients carrying an additional DC-targeted b 2 m transgene served as positive controls (40). However, when 2-dstimulated CD8 + T cells were transferred into such Ag-free hosts, they proliferated, regardless of MHC class I expression on peripheral cells (Fig.…”
Section: Cd8 + But Not Cd4 + T Cells Keep Dividing After a Transient mentioning
confidence: 99%
“…To determine whether the two APC types prime CTLs of different specificities, we used mice in which only DCs and thymic epithelial cells, and no other cell types, express MHCI molecules (26). These animals generate a normal CD8 + T-cell repertoire that can be primed only by MHCI + DCs (27). Using this model, we previously showed that DCs are sufficient to prime different virus-specific CTL responses (27)(28)(29) and to cross-present the model Ag OVA to OTI T cells (26).…”
Section: Significancementioning
confidence: 99%
“…These animals generate a normal CD8 + T-cell repertoire that can be primed only by MHCI + DCs (27). Using this model, we previously showed that DCs are sufficient to prime different virus-specific CTL responses (27)(28)(29) and to cross-present the model Ag OVA to OTI T cells (26). Surprisingly, DC-MHCI mice injected with rAd-GP mounted nearly exclusively K b /GP33-specific CTL responses, with strongly reduced D b /GP33-specific responses and undetectable D b /GP276-specific responses (Fig.…”
Section: Significancementioning
confidence: 99%